Partially bio-based processable polyimides based on aromatic diamine derived from cardanol - Shingte, Rahul D.; Tawade, Bhausaheb V.; Wadgaonkar, Prakash P. (green Materials, 2017)
A partially bio-based aromatic diamine, namely, 1,1-bis(4-aminophenyl)-3-pentadecylcyclohexane (BAC15) was synthesized starting from cardanol. A series of polyimides were synthesized by one-step high-temperature solution polycondensation of BAC15 with aromatic dianhydrides. Copolyimides were also synthesised by polycondensation of various compositions of BAC15 and 4,4’-oxydianiline with 3,3’,4,4’-biphenyl tetracarboxylic dianhydride. Inherent viscosities and number average molecular weights of (co)polyimides were in the range 0.33-1.4 dL/g and 14700-31900 g/mol, respectively, indicating formation of reasonably high molecular weight polymers. Polyimides were soluble in common organic solvents such as chloroform, dichloromethane and tetrahydrofuran and could be cast into transparent, flexible and tough films from their solutions in chloroform. (Co)polyimides exhibited Tg in the range 161–254 °C. The lowering of Tg could be attributed to the presence of flexible pentadecyl chains which act as “packing disruptive” groups. The temperature at 10% weight loss (T10) of (co)polyimides was in the range 490–515 °C demonstrating their good thermal stability. The virtue of solubility and large gap between Tg and T10 offers (co)polyimides opportunities of both solution as well as melt processability. Copolyimides containing pendent pentadecyl chains exhibited pretilt angle in the range 2.51-2.75° indicating their potential application as alignment layer in liquid crystal display devices.